(3GdcTa hGdHjGf Yf JaSjQ GdbQBfs - (3CHh ESMGb CMeO Hf eMeO Hf EHQGgje GdfjSGHhQj, GdKYdHj,J (B427 (3g` s ((3Gdajhe ef OjGQ eUQ s)
(3ChdgG (B:s
(3bGd GdTjN GdKYdHi QMeg Gddg (B: (3HMeO Gddg jaJM GdcdGe jSJfLM GdeWdH hGdeQGe CeG HYO aEf Gddg CcQefG HcQje cJGHg s
(3BNQgG (B:s
(3bhdg JYGdi (B( (3hEPG bjd dge GJHYhG eG CfRd Gddg bGdhG Hd fJHY eG CdajfG Ydjg BHGAfG (B) (3ef ShQI GdHbQI s
(3QhGjI GdEeGe CHj GdMSf Ydi Hf CMeO GdhGMOiHgG BKGQ JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B212s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs